'Blessed is the One who Stands in the Beginning' (L. 18): Revisiting Protological Eschatology in the Gospel of Thomas. (20th December 2021) - Joseph, Simon J
Abstract: Since its (re)discovery, the Gospel of Thomas has been a central site of debate in the study of Christian origins. Some scholars regard Thomas as a 'fifth gospel'; others an 'anti-Jewish' text dependent on the Synoptics. This article revisits one of Thomas 's most distinctive themes: protological eschatology. This article argues that logion 18 represents a worldview characterized by an Urzeit / Endzeit correlation, a motif relatively common in apocalyptic Judaism, and reminiscent of arguments from creation characteristic of the historical Jesus.